Texas Ranger John B. Jones and the Frontier Battalion, 1874-1881 - Miller, Rick, 1941- (Book collections on Project MUSE., 2012)
In 1874, the Texas legislature created the Frontier Battalion, the first formal, budgeted organization as an arm of state government of what historically had been periodic groups loosely referred to as Texas Rangers. Initially created to combat the menace of repeated raids of Indians from the north and from Mexico into frontier counties, the Battalion was led by an unusual choice: a frail, humorless Confederate veteran from Navarro County, John B. Jones. Under Jones's leadership, the Battalion grew in sophistication, moving from Indian fighting to capturing Texas's bad men, such as John Wesley.